Preparation of Er3+/Yb3+ co‐doped citrate microstructure fiber of large mode field and its 3.0 μm laser performance. Issue 4 (24th September 2018) - Zhou, Dechun; Jin, Danyang; Lan, ZhiDan; Bai, XueMei
Abstract: The double‐cladding Er 3+ /Yb 3+ co‐doped bismuth germanium gallate microstructure fiber of large mode, with the core diameter of 30.6 μm, the inner cladding air pore diameter of about 3.06 μm and a lattice constant of 10.2 μm is prepared by a bundle‐drawing method. The spectral characteristics at 975 nm wavelength were studied and the results show that the maximum fluorescence intensity and the high gain quality factor of the fiber core glass can be obtained when the molar ratio of Er 3+ to Yb 3+ is 0.5%:2% and its emission cross section is up to 10.9 × 10 −21 cm 2 . A stable laser output with a maximum power of 51.16 mW and a wavelength of 2710 nm was obtained in a microstructure optical fiber with a length of 160 mm employing a independently constructed fiber laser with a cascade structure, whose pump light power was 561 mW, the slope efficiency was 6.89%, the effective mode field area is about 576 μm 2 and the beam quality factor M 2 < 1.02. The double‐cladding Er 3+ /Yb 3+ co‐doped bismuth germanium gallate microstructure fiber of large mode has excellent laser properties and is an ideal optical fiber material for the development of the 3.0 μm laser.